Faktor Sosial yang mempengaruhi kepuasan Wisata di wilayah Danau Toba, Sumatera Utara - Ronnie M T Sirait; Runggu Besmandala Napitupulu; Dameria Girsang; Agam Sinaga; Lisan Hot Pandiangan (Akademi Pariwisata Darma Agung, 2018)
The research objective is to find out: the elements of social capital in the Lake Toba region; The main components of social capital that affect tourist satisfaction in the Lake Toba region; The main component with the highest relationship or influence on social capital. Questionnaires were distributed to 170 respondents aged 17 years and over. International tourists as many as 19 people and domestic tourists as many as 151 people. Data is reviewed by exploratory factor analysis techniques. The results of the study are: Social capital that influences tourist satisfaction includes 15 components; Extraction of components produces 3 main components; The main components include: Tourist satisfaction with community trust in the Lake Toba area; Tourist satisfaction with community norms in the Lake Toba region; Tourist satisfaction with the social network of the community in the Lake Toba region; The highest average loading factor for component 1.